ANALISIS PENERAPAN PEMBELAJARAN TEMATIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 008 SUNGAI KUNING KECAMATAN SINGINGI - Asmayarni Asmayarni; Sopiatun Nahwiyah; Andrizal Andrizal (Universitas Islam Kuantan Singingi, 2020)
The ability of teachers to carry out their duties can be said to be good if they have basic abilities or absolute teacher competence. One of them is pedagogical ability, namely the ability to manage student learning, this competency can be seen from the abilit y to plan teaching and learning programs, the ability to carry out interactions or manage the teaching and learning process and the ability to conduct assessments. Based on observations of the ability of teachers is caused by several factors, namely: thelimitations of teachers in using electronic media that are still not available in schools, then personality factors related to behavior, authority, and character that will affect the learning process. The formulation of the problem in this study is how the application of thematic learning in Islamic Religious Education subjects at public elementary school008 Sungai Kuning District Singingi. The population and sample in this study were one Islamic Religious Education teacher at public elementary school 008 Sungai Kuning , Singingi District. This study includes research with a qualitative descriptive approach, with data collection techniques through observation, interviews and documentation. And data analysis techniques used are reducing data, presenting data and drawing conclusions. The results showed that the application of thematic learning in Islamic Religious Education subjects was